If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -214 + -1(-87) = x Multiply -1 * -87 -214 + 87 = x Combine like terms: -214 + 87 = -127 -127 = x Solving -127 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -127 + -1x = x + -1x Combine like terms: x + -1x = 0 -127 + -1x = 0 Add '127' to each side of the equation. -127 + 127 + -1x = 0 + 127 Combine like terms: -127 + 127 = 0 0 + -1x = 0 + 127 -1x = 0 + 127 Combine like terms: 0 + 127 = 127 -1x = 127 Divide each side by '-1'. x = -127 Simplifying x = -127
| 6=-5/w-5 | | -10n=20 | | 1/2x=x+10- | | x+(x-18)=150 | | 3(2y-6)=-9(y-8) | | 13x+1y=25 | | [-2x+4]=4 | | -3[2t+1]=9 | | -10=-4v-v | | 8x+1=10-5x | | 3/4[8t-12]=6(t-1) | | 2x-5x=y | | a+bi+6(a-bi)=7 | | 27rst+27tsr= | | 3/4[8t-12]=6(1-1) | | 13+-7-10x=2 | | -5b=25 | | 12*90= | | 5+2(x-2)=18 | | v+3=-1 | | 9/4t^-1 | | (-4)(u+2)=((3)(2u+4))+4 | | 10=-4v-v | | [3z-2]+5=9 | | (f/2)-4=1 | | 112+2x=22-4x | | 2[4x+1]-5=1 | | -24=2x-x+6 | | p+9=0 | | 1/2[2x-1]-3=1 | | 9x^5/27x^2 | | 270/3[(4-3)3-(-9)]-53 |